2021
DOI: 10.1136/bmjgh-2021-005108
|View full text |Cite
|
Sign up to set email alerts
|

Flourishing: migration and health in social context

Abstract: Health and the capacity to flourish are deeply intertwined. For members of vulnerable migrant groups, systemic inequalities and structural forms of marginalisation and exclusion create health risks, impede access to needed care and interfere with the ability to achieve one’s full potential. Migrants often have limited access to healthcare, and they frequently are portrayed as less deserving than others of the resources needed to lead a healthy and flourishing life. Under these circumstances, clinicians, health… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Expanding on the notion of well-being, Willen et al (2021) further explores the relationship between ourishing and health among migrants (Willen et al, 2021). For migrants, systemic inequalities and structural forms of marginalization and exclusion create health risks, impede access to needed care and interfere with their ability to ourish (Willen et al, 2021). Johan Galtung, a well-known Norwegian sociologist and liberation theologian coined the term 'structural violence' in the 1960s to describe longstanding social structures-economic, political, legal, religious, and cultural-that impede individuals and groups from ourishing or reaching their full potential (Galtung, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…Expanding on the notion of well-being, Willen et al (2021) further explores the relationship between ourishing and health among migrants (Willen et al, 2021). For migrants, systemic inequalities and structural forms of marginalization and exclusion create health risks, impede access to needed care and interfere with their ability to ourish (Willen et al, 2021). Johan Galtung, a well-known Norwegian sociologist and liberation theologian coined the term 'structural violence' in the 1960s to describe longstanding social structures-economic, political, legal, religious, and cultural-that impede individuals and groups from ourishing or reaching their full potential (Galtung, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study with French migrants demonstrated how if asylum seekers were granted access to work after one month or less, negative attitudes between migrants and French nationals would be drastically reduced, therefore, positively impacting social cohesion (Chenus, 2019). These limitations imposed by macro-level legal barriers ultimately harmed migrants' capacity to ourish within their host society (Willen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…4,37 Such issues have described a perceived idea of 'deservingness' that categorizes patients, particularly migrant peoples, as more or less deserving of access to quality health care. 38 There are few published data on health care needs of migrant peoples in transit through Latin America en route to the United States. Gray literature from UN and other international nongovernmental organizations suggest the greatest health needs include treatment of fever, skin problems, diarrhea and prenatal care.…”
Section: Discussionmentioning
confidence: 99%